Enhanced reactive H2S adsorption using carbon nanofibers supported with Cu/CuxO nanoparticles - Bajaj, Bharat; Joh, Han-Ik; Jo, Seong Mu; Park, Ji Hye; Yi, Kwang Bok; Lee, Sungho (ELSEVIER SCIENCE BV, 2018)
Activated carbon nanofibers (ACNFs) modified with Cu/CuxO nanoparticles were prepared from the carbonization of electrospun polyacrylonitrile/copper precursor nanofibers, followed by a mild-activation process. Dynamic breakthrough test for hydrogen sulfide adsorption were conducted at 300 degrees C, and more than 15 times enhancement in the breakthrough time is observed for ACNF with the nanoparticles (938 min) compared to pure ACNF (62 min). The dramatic enhancement is attributed to the presence of well dispersed Cu/CuxO nanoparticles, which exposed on the surface during the mild activation. In addition, ACNFs as supporting layers plays an important role in preventing aggregation of nanoparticles. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: ACTIVATED CARBON; HYDROGEN-SULFIDE; COPPER; DESULFURIZATION; REGENERATION; TEMPERATURE; PERFORMANCE; REMOVAL; FIBERS; OXIDES